Immunological landscape of colorectal cancer: tumor microenvironment, cellular players and immunotherapeutic opportunities - Andac-Aktas, Adile Buse; Calibasi-Kocal, Gizem (Frontiers in Molecular Biosciences, 2025)
Colorectal cancer (CRC) remains one of the most lethal malignancies worldwide, with outcomes shaped not only by genetic alterations but also by the complexity of the tumor microenvironment (TME). The TME encompasses stromal and endothelial cells, extracellular matrix components, gut microbiota, and a diverse array of immune cells that dynamically interact to influence tumor initiation, progression, and therapeutic response. This review delineates the immunological landscape of CRC, highlighting the dual functions of innate immune cells—including tumor-associated macrophages, natural killer cells, dendritic cells, neutrophils, and mast cells—and adaptive immune players such as cytotoxic T lymphocytes, helper T-cell subsets, and B/plasma cells. These cellular interactions contribute to the heterogeneity between immunologically “hot” microsatellite instability-high (MSI-H) tumors, which are highly responsive to immunotherapy, and “cold” microsatellite-stable (MSS) tumors, which remain resistant. Key mechanisms of immune evasion, such as cancer immunoediting, checkpoint signaling, and exosome-mediated communication, are examined alongside prognostic tools like the Immunoscore that serve as biomarkers of immune infiltration. Emerging immunotherapeutic strategies, including checkpoint blockade, macrophage reprogramming, natural killer cell agonists, and microbiome modulation, are discussed with emphasis on both their promise and limitations in CRC management. By integrating current insights into immune–tumor interactions, the review underscores opportunities for developing personalized, TME-targeted interventions to improve CRC outcomes.